Cognitive Behavior Therapy Teknik Thought Stopping untuk Mengurangi Insecure - Lianasari, Dewi; Ria, Nursidah; Kurniati, Astiwi (Guidance and Counseling Study Program, Pattimura University, 2023)
In recent years, many insecure phenomena have appeared in several individuals, without exception for students, so students prefer to think negatively about themselves and cause themselves to lose confidence because there is something that makes them threatened and insecure. Therefore, there is a need for handling students who have a high level of insecurity, so that students can be more confident in developing their potential.This study was aimed at looking at the effectiveness of Cognitive Behavior Therapy group counseling with the Thought Stopping Technique to reduce the level of insecurity. The method used in this research is pre experiment with One Group Pre test Post Test Design. In this study the sample was chosen not randomly (purposive sampling) from 12 students in class XI.OTKP SMK Muhammadiyah Magelang City taken a sample of 9 students as members experimental group. This research was conducted in 6 meetings. MThe method used as data analysis is using parametric statistics Sample T-Test with SPSS 26 Software. The results of the study indicate that the Cognitive Behavior Therapy group counseling Thought Stopping technique has an effect on reducing the level of insecurity. This can be proven based on the results of the Paired Sample T-Test analysis with a significant probability value of 0.001 <0.05.